Safety precautions in the usage of extension cords by students in halls and hostels - Divine Tuinese Novieto; Frank Kulor; Elisha D. Markus; Michael Wellington Apprey (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
This paper presents the evaluation of the safety measures adopted by Ho Technical University (HTU) students in the use of power extension cords in their halls and hostels, along with their safety considerations for properly selecting these cords to avert fire outbreaks or prevent them from becoming a potential fire hazard. Whenever extension cords are utilized inappropriately it can lead to fire or electric shock perils. The assessment of the awareness level of safety practices is yet to be rigorously pursued as an agenda towards extension cord usage in institutions and agencies perceived to be high energy consumers where fire outbreaks occur frequently. A quantitative research approach was adopted, using a questionnaire for data collection. The findings revealed that about 52% of the respondents did not know the current and power ratings and the effects of overloading the extension cord. It was recommended that consumers purchase extension cords that have been endorsed by an autonomous testing laboratory, whereas the university should immediately organize a seminar to educate the staff and students about the use of the extension cord.